The Responsibilities of the Substitute PPAT for Cancellation of Sales and Purchase Deeds Ignoring the Principle of Accuracy - Fairuzzarah, Nisrina (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to find out and analyze the juridical implications of canceling a sale and purchase deed made by a Substitute PPAT, to find out and analyze the responsibilities of a Substitute PPAT for canceling a sale and purchase deed that ignores the principle of accuracy, and to find out and analyze examples of deeds that can be declared null and void. law. The approach method used in this research is normative juridical with the research specification used is descriptive analysis. This study used a data collection method, namely library research. This study uses qualitative analysis techniques. Based on the research, it was concluded that the juridical implications of canceling the sale and purchase deed made by the Substitute PPAT, then the deed he made can have the power of the deed under the hand or null and void. This relates to the cancellation of the unregistered Sale and Purchase Deed which has implications for being legally flawed. So that the Deed of Sale and Purchase is null and void by law. Substitute PPATs who commit negligence by ignoring the principle of accuracy are subject to administrative sanctions in the form of temporary dismissal to permanent dismissal. The responsibility of the Substitute PPAT for the cancellation of the sale and purchase deed that ignores the principle of accuracy, the cancellation of the sale and purchase deed that occurs due to the negligence of the Substitute PPAT. The cancellation of the sale and purchase deed must be in accordance with the applicable procedures. However, what happened was that the cancellation of the sale and purchase deed caused problems which were not registered at the Land Office.Keywords: Accuracy; Responsibility; Substitute.